Шляхи оптимізації державного боргу в сучасних умовах - Борисюк, Олена Володимирівна; Borysiuk, Olena V. (Східноєвропейський національний університет ім. Лесі Українки, 2015)
У статті досліджено формування нового погляду на проблему зростання державного боргу України в контексті загострення боргової безпеки. Оцінено сучасний стан державного боргу України та визначено основні заходи, які доцільно здійснити для оптимізації державного боргу України. Article posvyaschena Formation of a new glance at the problem of state-owned debt growth in the context of Ukraine exacerbations dolhovoy security. Otseneno Modern STATUS state-owned debt of Ukraine and opredelenы Main activities of, kotorыe advisable for optimization osuschestvyt state-owned debt of Ukraine. Established something Strategy Formation and Maintenance of market hosudarstvennыh zaymstvovanyy dolzhna bazyrovatsya on scientific principles obosnovannыh. Wikipedia articles in Particular posvyascheno Evaluation and Maintenance of state-owned vnutrenneho On external debt of Ukraine. Rassmotreno Strategy for debt management hosudarstvennыm Years 2013–2015, Implementation kotoroj pozvolyt dostych to End 2015 Manuscript Volume Reduction relationships for state-owned debt vnutrennemu GDP. Accordingly bыly vыdelenы goal uppravlynnya Gosudarstvennoye debt and path s decision. In this set, something vazhnoe importance ymeet pryostanovlenyy ottoka ynostrannoho Banking IZ capital of Ukraine, Increase pryvlekatelnosty hosudarstvennыh tsennыh paper How to nerezydentov and Ukrainian investors, and as for the population.
Ways Optimization State-owned Debt in Modern Conditions
Keywords: державний борг; боргова безпека; валовий зовнішній борг; державний зовнішній борг; середньострокова стратегія управління державним боргом; public debt; dolhovaya bezopastnost; public debt management; gross external debt; domestic government debt; medium-term strategy for public debt management